2017
DOI: 10.1002/2017jc012978
|View full text |Cite
|
Sign up to set email alerts
|

Rollover of Apparent Wave Attenuation in Ice Covered Seas

Abstract: Wave attenuation from two field experiments in the ice‐covered Southern Ocean is examined. Instead of monotonically increasing with shorter waves, the measured apparent attenuation rate peaks at an intermediate wave period. This “rollover” phenomenon has been postulated as the result of wind input and nonlinear energy transfer between wave frequencies. Using WAVEWATCH III®, we first validate the model results with available buoy data, then use the model data to analyze the apparent wave attenuation. With the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 33 publications
11
48
2
Order By: Relevance
“…Attenuation was shown to increase monotonically with wave frequency in all except one case. The apparent rollover in attenuation rates at high wave frequencies (observed reported by Kohout et al 2011 andLi et al 2017) did not occur in our experiments. Comparisons between similar types of ice showed that attenuation rates also increase with ice cover thickness.…”
Section: Discussionsupporting
confidence: 62%
“…Attenuation was shown to increase monotonically with wave frequency in all except one case. The apparent rollover in attenuation rates at high wave frequencies (observed reported by Kohout et al 2011 andLi et al 2017) did not occur in our experiments. Comparisons between similar types of ice showed that attenuation rates also increase with ice cover thickness.…”
Section: Discussionsupporting
confidence: 62%
“…Journal of Geophysical Research: Oceans reported for a case in Antarctic MIZ in Kohout et al (2014) might also be partly due to this wind input. Most recently, Li et al (2017) confirmed that roll-over in the same Antarctic case likely is a result of wind input to the highest frequencies. The wind input causes it to appear that less attenuation occurred, when comparing the net difference between two measurements (i.e., two buoys).…”
Section: 1002/2018jc013766mentioning
confidence: 99%
“…Similarly, the details of wave and wind coupling in the presence of ice are not fully understood. Although wind input is reduced in ice (Zippel & Thomson, 2016), there may still be sufficient wind input to offset some of the attenuation (Li et al, 2015b(Li et al, , 2017.…”
Section: 1002/2018jc013766mentioning
confidence: 99%
“…A summary of the least-squares fits with the laboratory data can be found in Table 1. Interpreting field data is decidedly more difficult as the wave field often consists of a broadband spectrum and the wind input and nonlinear terms can also have a non-negligible contribution to the spectral energy (Li et al, 2015(Li et al, , 2017. It is important to keep this in mind, that the wave dissipation due to the sea ice might not be the dominant process affecting the wave spectral energy, when comparing field observations with theoretical models for wave dissipation.…”
Section: Comparisons With Previous Experimentsmentioning
confidence: 99%